Statistics for the engineering and computer sciences - Mendenhall, William; Sincich, Terry (California : Dellen Publishing Company, 1984)
This is a text for a two-semester introductory course in statistics for students majoring in engineering, the physical sciences, or computer science.
1. Some Basic concepts -- 2. Using the computer -- 3. Probability -- 4. Discrete random variables -- 5. Continuous random variables -- 6. Bivariate probability distribution -- 7. Sampling distribution -- 8. Estimation -- 9. Tests of hypotheses -- 10. Simple linear regression analysis -- 11. Multiple regression analysis -- 12. Introduction to model building -- 13. The analysis of variance for designed experiments -- 14. The analysis of variance for nested sampling designs -- 15. The analysis of enumerative data -- 16. Nonparametric statistics -- 17. Applications: product and system reliability -- 18. Applications: quality control.
Includes index.
Keywords: ENGINEERING -- STATISTICS